Improving Learning Outcomes in Electrical Circuits Through STAD Cooperative Learning with Structured Tasks - Wadjdi, Faried (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to evaluate the effectiveness of the STAD (Student Teams-Achievement Divisions) cooperative learning model in enhancing students' understanding of electrical circuit concepts in the Electrical Engineering Education Study Program. The research method employed was an experimental design with a pretest-posttest approach involving 56 respondents divided into two groups: an experimental group applying the STAD model and a control group using conventional learning methods. Data were collected through pretests and posttests and analyzed using Jamovi 2022 software. The results indicate that the average score of the experimental group increased from 8.96 in the pretest to 13.7 in the posttest, with a significant effect size of -4.05. These findings suggest that the implementation of the STAD model not only improves student learning outcomes but also fosters collaboration and interaction among students. Therefore, it is recommended that the STAD cooperative learning model with structured tasks be more widely adopted to enhance conceptual understanding of Electrical Circuits.